Selenium Levels based on Various Menopause Complaints Assessed by Menopause-specific Quality of Life Questionnaire before and after Selenium Intervention - Hisworo, Muhammad Ramadhan; Siregar, Muhammad Fidel Ganis; Pasaribu, Hotma Partogi; Marpaung, Johny; Rusda, Muhammad; Dina, Sarah; Ardiansyah, Edy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Menopausal symptoms can greatly affect a woman’s personal, social, and work life. Selenium functions as a cofactor for glutathione peroxidase and helps minimize oxidative damage through cellular metabolism in postmenopausal women when estradiol production decreases, antioxidant protection is lost and therefore oxidative stress is increased. AIM: The aim of the study was to evaluated effect of selenium supplementation on selenium levels based on menopausal complaints assessed by menopause-specific quality of life questionnaire (MENQOL). MATERIALS AND METHODS: This research is an analytical study with quasi-experimental pre-test and post-test one group only design. The research was conducted on all postmenopausal women in Medan who were aged >51-years-old and met inclusion and exclusion criteria. The research subjects underwent blood tests to assess serum selenium levels. If data were normally distributed, dependent T test will be used, while if data were not normally distributed, Wilcoxon test will be used. The analysis results were stated to be significant with p < 0.05. RESULTS: Mean selenium serum levels before selenium administration were 93.20 ± 17.253 μg/L which increased to 132.12 ± 19.866 μg/L after selenium administration. Comparison test results of selenium levels before and after administration found p = 0.000 (p < 0.05), which means there was a significant difference of selenium serum levels before and after selenium administration. Besides that, there were no significant scores difference in aspects of vasomotor disorders (p = 1.000 [p > 0.05]), psychosocial disorders (p = 0.090 [p > 0.05]), physical disorders (p = 0.323 [p > 0.05]), and sexual disorders (p = 0.959 [p > 0.05]) between before and after selenium administration. CONCLUSION: Total MENQOL scores and complaints based on aspects of vasomotor, psychosocial, physical, and sexual disturbances did not show statistically significant changes after administration selenium tablets 100 mcg/day for 7 days.